2010
DOI: 10.1104/pp.109.152009
|View full text |Cite
|
Sign up to set email alerts
|

Channel-Like Characteristics of the Low-Affinity Barley Phosphate Transporter PHT1;6 When Expressed inXenopusOocytes

Abstract: Remobilization of inorganic phosphate (P i ) within a plant is critical for sustaining growth and seed production under external P i fluctuation. The barley (Hordeum vulgare) transporter HvPHT1;6 has been implicated in P i remobilization. In this report, we expressed HvPHT1;6 in Xenopus laevis oocytes, allowing detailed characterization of voltage-dependent fluxes and currents induced by HvPHT1;6. HvPHT1;6 increased efflux of P i near oocyte resting membrane potentials, dependent on external P i concentration.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
65
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 44 publications
1
65
0
Order By: Relevance
“…Expression Levels of the Genes Related to Low-Affinity Pi Transporters Are Correlated with PUE HvPHT1;6 is a low-affinity Pi transporter (Preuss et al, 2010). It is expressed in both shoots and roots (Huang et al, 2008) and especially in phloem tissues of the leaf (Rae et al, 2003), suggesting that HvPHT1;6 plays a role in Pi remobilization in the whole plant.…”
Section: Genetic Variation In P-acquisition Efficiency In Four Distinmentioning
confidence: 99%
See 2 more Smart Citations
“…Expression Levels of the Genes Related to Low-Affinity Pi Transporters Are Correlated with PUE HvPHT1;6 is a low-affinity Pi transporter (Preuss et al, 2010). It is expressed in both shoots and roots (Huang et al, 2008) and especially in phloem tissues of the leaf (Rae et al, 2003), suggesting that HvPHT1;6 plays a role in Pi remobilization in the whole plant.…”
Section: Genetic Variation In P-acquisition Efficiency In Four Distinmentioning
confidence: 99%
“…HvPHT1;6 is expressed in both shoots and roots (Huang et al, 2008) and localized in the leaf phloem tissue (Rae et al, 2003). It displays unsaturated uptake in a millimolar range of Pi concentrations when expressed in oocytes (Preuss et al, 2010), suggesting that HvPHT1;6 is involved in Pi retranslocation. HvPHT1;7 is specifically expressed in green anthers (Druka et al, 2006), and HvPHT1;8 is a mycorrhiza-specific gene (Glassop et al, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In annual plants, Himelblau and Amasino (2001) have found that about 80% of P is removed from senescing Arabidopsis (Arabidopsis thaliana) leaves. In barley (Hordeum vulgare), expression of the Pi transporter HvPT6, likely involved in Pi remobilization (Preuss et al, 2010), was increased as leaves aged (Rae et al, 2003).…”
mentioning
confidence: 99%
“…Recently, Nagarajan et al (2011) reported that the Arabidopsis pht1;5-1 mutant had higher shoot P content compared with the wild type, while the P content in roots was reduced under Pi-replete conditions, suggesting that Pht1;5 may mobilize Pi between source and sink tissues. In addition, Preuss et al (2010) explored the characteristics of the low-affinity barley (Hordeum vulgare) PiT PHT1;6 using the Xenopus laevis oocyte expression system, implying that it may play a Pi-transport role at Pi-sufficient conditions in plants.…”
mentioning
confidence: 99%